Toby the explorer—An interactive educational game for primary school pupils - Trivodaliev, Kire; Stojkoska, Biljana; Mihova, Marija; Kaevikj, Nenad; Kostadinovska, Angela (IEEE, 2016)
Technology enhanced education has been recently established as a new approach for all stages of education in developing countries, especially in Macedonia. Although computer games are often given little attention we believe that within the vast amount of technologies and instruments used to achieve the needed improvements it is computer games that are playing the central role in delivering the desired effects, in particular to children and teenagers. In this paper we present the “Toby the Explorer”, an interactive educational game for primary school students. We show in depth the engineering behind the game, its design and structure. We also give an insight and evaluation of the importance of the game in enhancing the educational process. Our results show that the learning process is regarded as more easy and fun by the students that learned by playing, but also it increased their interest in learning other subjects not included explicitly in the game.
Keywords: Educational games; Game-based learning; eLearning; Desktop games; Games for kids